Armed Citizens or traitors to the patria? Indigenous participation in the Bolivian revolutions of 1870 and 1899 - Irurozqui, Marta (2006)
This article compares the  indigenous armed participation in the Bolivian civil wars of 1870 and 1899 paying special attention to this population’s changing access to citizenship. The alliance between the indians and the militaries shows, in the first place, how indians were neither alien to the process of national construction nor aloof from the political conceptions and projects of the nineteenth century, but that they became, moreover, central subjects in the institutionalization and territorial rearrangement of the State insofar as they assumed the narrative of citizenship and national cooperation as their own, on behalf of their own defense as a group. Secondly, the complex image of the “soldier/nacional/armed citizen” suggests the capacity of armed conflicts to generate changes of perception about citizenship and citizen belonging, and to influence the processes of indianization and reindianization of identities.